Thrown out with the bargain - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Report of baseline study on land and property grabbing By Emang Basadi Women s Association et al., Lightbooks Publishers, 2002. 48pp. ISBN 9991271252 GBP 8.95 Euro 13.40